Lubiprostone Decreases the Small Bowel Transit Time by Capsule Endoscopy: An Exploratory, Randomised, Double-Blind, Placebo-Controlled 3-Way Crossover Study. (29th December 2014) - Matsuura, Mizue; Inamori, Masahiko; Endo, Hiroki; Matsuura, Tetsuya; Kanoshima, Kenji; Inoh, Yumi; Fujita, Yuji; Umezawa, Shotaro; Fuyuki, Akiko; Uchiyama, Shiori; Higurashi, Takuma; Ohkubo, Hidenori; et al.
Abstract : The aim of this study was to investigate the usefulness of lubiprostone for bowel preparation and as a propulsive agent in small bowel endoscopy. Six healthy male volunteers participated in this randomized, 3-way crossover study. The subjects received a 24 μ g tablet of lubiprostone 60 minutes prior to the capsule ingestion for capsule endoscopy (CE) and a placebo tablet 30 minutes before the capsule ingestion (L-P regimen), a placebo tablet 60 minutes prior to CE and a 24 μ g tablet of lubiprostone 30 minutes prior to CE (P-L regimen), or a placebo tablet 60 minutes prior to r CE and a placebo tablet again 30 minutes prior to CE (P-P regimen). The quality of the capsule endoscopic images and the amount of water in the small bowel were assessed on 5-point scale. The median SBTT was 178.5 (117–407) minutes in the P-P regimen, 122.5 (27–282) minutes in the L-P regimen, and 110.5 (11–331) minutes in the P-L regimen (P = 0.042 ). This study showed that the use of lubiprostone significantly decreased the SBTT. We also confirmed that lubiprostone was effective for inducing water secretion into the small bowel during CE.